Establishment of PM10 and PM2.5 emission inventories from wind erosion source and simulation of its environmental impact based on WEPS-Models3 in southern Xinjiang, China. (1st March 2021) - Liu, Yaxin; Teng, Yu; Liang, Shuang; Li, Xiaoli; Zhao, Jingwen; Shan, Mei; Chen, Li; Yu, Hai; Mao, Jian; Zhang, Hui; Gao, Shuang; Sun, Yanling; et al.
Abstract: Southern Xinjiang located in the far northwest of China is experiencing serious particulate matter (PM) pollution. The wind erosion has been recognized as a great contributor of PM10 and PM2.5 concentrations in southern Xinjiang. In this study we developed a method that used the Wind Erosion Prediction System (WEPS) to establish the PM10 and PM2.5 emission inventories from the wind erosion source in southern Xinjiang with a 10 km × 10 km spatial resolution and a temporal resolution of one month. The PM10 and PM2.5 emission inventories from wind erosion sources were provided as input to the Models3/SMOKE (Sparse Matrix Operator Kernel Emission). The Community Multi-scale Air Quality (CMAQ) model was employed to simulate PM10 and PM2.5 concentrations from wind erosion source and the results were compared with the monitoring data to verify the emission inventories. The total PM10 and PM2.5 emissions were 12 × 10 6 t and 4 × 10 6 t, respectively, and the emission per unit area were 14.6 t/km 2 and 4.9 t/km 2, respectively, in southern Xinjiang in 2016. The PM10 and PM2.5 emissions per unit area were highest in Kashi being 19.1 t/km 2 and 9.1 t/km 2, respectively. The total emissions peaked at 5.4 × 10 6 t/km 2 in PM10 and 1.4 × 10 6 t/km 2 in PM2.5 in Bazhou. The PM10 and PM2.5 emissions were highest in spring, followed by summer, winter and autumn. The Normalized Mean Error (NME) between the predicted monthly average PM10 and PM2.5 concentrations from wind erosion source and the results from multiplying the monitoring data by the source apportionment results of PM10 and PM2.5 were 25.3% and 26.1%, respectively, which indicated that the accuracies of the PM10 and PM2.5 emission inventories from wind erosion source in southern Xinjiang were satisfactory. Highlights: PMs emission inventories of wind erosion source were established using WEPS model. PMs emission inventories of wind erosion source were verified based on CMAQ. The ratios of PM2.5 to PM10 emissions were derived from the wind tunnel experiment.